Exploring factors that influence wine tourist satisfaction - a research proposal - Thomas, Ben; Quintal, Vanessa (School of Marketing, Curtin Business School, 2010)
This paper aims to conceptualise the commonly referred to "winescape" in wine tourism literature and develop a scale to measure its effects on wine tourist satisfaction. Integrating theoretical underpinnings from services and tourism marketing into existing wine tourism literature a framework for the proposed winescape is presented and contains winescape aesthetics, winescape layout and signage, winescape features, winescape activities and winescape service staff. It is proposed that these constructs will all have a positive effect on wine tourist satisfaction with a wine region. Theoretical, methodological and managerial contributions of this study are also discussed.